The Rise of Digital PHMDPS: An In-Depth Study of Medication Delivery Innovations in Indonesian Hospitals - Mochammad Sucahyono; V. Rudy Handoko; Rachmawati Novaria (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The adoption of medication delivery services by hospitals in Indonesia reflects a significant upward trend in the transformation of the national healthcare landscape. This development is largely driven by the increasing demand for patient convenience and equitable access to essential medicines, alongside the rapid advancement of digital health technologies and the disruption of traditional healthcare systems, particularly during the COVID-19 pandemic. To explore this phenomenon, this study employed a systematic literature review method, analyzing diverse sources comprising government reports, hospital websites, official social media posts, online news articles, and prior research. The objective was to synthesize findings on how Indonesian hospitals—both public and private—have implemented and digitalized their Patient Home Medication Delivery Programs (PHMDPs). Key findings reveal a growing prevalence of PHMDPs, supported by various delivery models, ranging from internal logistics systems to partnerships with third-party couriers and telemedicine platforms. Digitalization emerges as a central enabler, facilitating seamless integration of e-prescriptions, automated logistics, and mobile health applications. Despite the growing adoption, the regulatory framework remains in flux, and hospitals face several challenges, including logistical complexity, compliance issues, and cost sustainability. This study contributes a comprehensive overview of PHMDPs in Indonesia, highlighting best practices and offering insights for scalable, patient-centered innovations in digital pharmaceutical services.